Performance and the philosopher's costume: Richard Shusterman as the Man in Gold. Issue 1 (1st June 2020) - Mullis, Eric
This article discusses philosopher Richard Shusterman's artistic collaboration with Yann Toma which entails the use of costume, photography and public performance. The project advances the interdisciplinary field of somaesthetics and raises questions about conventions of professional philosophy, including what philosophers conventionally wear and how philosophical inquiry is advanced. Aspects of costume theory and contemporary movement performance are used to analyse Shusterman's autobiographical methodology and the project's performative aims.